Genetic polymorphism and relationship analyses of standard poodle and bichon frise groups based on 19 short tandem repeat loci - Shuyan Mei; Jinlong Yang; Jianping Li; Xin Xiong; Menglei Wang; Zhichao Zhao; Yuxin Guo; Yajun Deng (Wolters Kluwer Medknow Publications, 2023)
Context: As the increasing number of pet canines, the identification of canine has attracted much attentions in the forensic field, however, the genetic diversities of pet canines still remained unknown. Aims: To explore genetic polymorphisms of 19 short tandem repeat (STR) loci and genetic relationships between the two studied canine groups and reference group. Subjects and Methods: In the present study, genetic polymorphisms of 19 STR loci and a sex-linked zinc finger locus were analyzed in a total of 594 canines in Standard Poodle and Bichon Frise groups from China. Results: A total of 166, 159 alleles were observed in the Standard Poodle, Bichon Frise groups with the corresponding allelic frequencies ranging from 0.0030-0.6108 to 0.0012-0.6148, respectively. The combined discrimination power and probability of exclusion of 19 STR loci in Standard Poodle and Bichon Frise groups were 0.9999999999999497, 0.999962884; and 0.99999999999999995, 0.999965955, respectively. Furthermore, the genetic distances between the two canine groups and Labrador retriever group were calculated, and the results indicated that Standard Poodle and Bichon Frise groups showed a closer genetic relationship, while the two canine groups had distant genetic relationships with Labrador retriever group. The result of population genetic structure revealed that genetic component distributions in the three canine groups were different. The predicted accuracies of the constructed random forest prediction model for three validation sets (25% individuals randomly selected from three populations with 808 individuals) were higher than 0.9, especially for the individuals in validation set from the Bichon Frise group is 1. Conclusions: The 19 STR loci could be used for individual identification, canine breed identification and paternity testing in the two canine groups.